Meminimalisir Kadar Detergen Dengan Penambahan Koagulan dan Filtrasi Media Saring pada Limbah Kamar Mandi - Haderiah, Haderiah; Dewi, Novi Utami (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Detergent is a mixture of various materials, which are used to help cleanup and made from ingredients derived petroleum. Detergent products are now used by almost all the residents for various purposes such as washing clothes and furniture as well as other cleaning materials. Chemical oxygen Demand (COD) is the amount of oxygen needed to oxidize the organic substances present in the water sample or the amount of oxygen is needed to oxidize organic substances into CO2 and H2O. Figures COD is a measure for water pollution by organic substances that can naturally oksidasikan through microbiological processes, and result in reduced dissolved oxygen in the water. The purpose of this study was to determine efficiency of coagulation and filtration media using sand and zeolite in the lower levels of detergent and COD in wastewater bathroom.This study is an experimental study, namely to determine the efficiency of coagulation and filtration media using sand and zeolite in the lower levels of detergent and COD in the waste water showers. The results showed that the levels of detergent effluent treatment bath after the coagulation and filtration processes to decrease the levels of detergent = 99.89%, COD = 75.43%. From these results it is suggested that the waste from the bathroom processed before it is disposed ke lingkungan. With the hope of effluent produced can reduce levels of pollutants or can meet the standard of effluent quality standards for household activities in accordance South Sulawesi Governor Decree No. 69 in 2010. Keywords : Detergent, COD, Coagulation, Sand, and Zeolite<br style="text-transform: none; line-height: normal; text-indent: 0px; letter-spacing: normal; font-style: normal; font-variant: normal; font-weight: normal; word-spacing: 0px; white-space: normal; orphans: 2; widows: 2; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />